Effects of prolonged load carriage on gait, physiological and neuromuscular performance in experienced military personnel - Adriane Mara de Souza Muniz; Míriam Raquel Meira Mainenti; André de Abreu Castilho Diel; Eduardo Martins Silva; Rodrigo Rico Bini; Luciano Luporini Menegaldo (Sport Sciences for Health, 2026)
Abstract Background Load carriage has been widely studied; however, gait and jump performance assessment after prolonged military load carriage in experienced soldiers has received less attention. Objective This study aimed to map neuromuscular, physiological, and gait changes associated with long-distance simulated load carriage in experienced military personnel. Sixteen male soldiers performed a 12-km simulated military march with a 30-kg load on a treadmill. Gait and vertical jump characteristics were evaluated pre- and post-task using ground reaction force (GRF) measurements. Heart rate (HR), pelvic accelerometry, and Borg rating of perceived exertion (RPE) data were collected at the beginning and end of the march. Results Decline in lower-limb mechanical performance following prolonged load carriage was evidenced by reduced gait propulsive forces (second peak of force: 1.17 ± 0.05 vs 1.14 ± 0.05%body weight, p = 0.009, d =0.88; propulsive force: 0.25 ± 0.02 vs 0.24 ± 0.01%body weight, p =0.043, d =0.64) and jump power during the eccentric braking phase (− 21.6 ± 4.5 vs − 19.6 ± 4.5 Watts/kg, p =0.008, d =0.91) along with increased concentric jump power (49.4 ± 5.8 vs 51.0 ± 6.5 Watts/kg, p =0.008, d =0.92). Reduced cadence (112.1 ± 5.81 vs 109.4 ± 5.74 steps/min, p =0.043, d =0.64) with elevated HR reserve (26.0 ± 6.8 vs 36.9 ± 7.5%, p =0.006, r =0.82) and RPE (2.7 ± 0.7 vs 5.0 ± 0.7, p